Penilaian Tingkat Kapabilitas Tata Kelola Teknologi Informasi Menggunakan Kerangka Cobit - Priyatna, Ade; Sanwani, Sanwani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study analyzes the capability level of information technology (IT) governance using the COBIT framework, focusing on the APO (Align, Plan, and Organize) and MEA (Monitor, Evaluate, and Assess) domains. In the rapidly evolving digital era, IT plays a crucial strategic role in supporting operational efficiency, product innovation, and customer service enhancement. However, suboptimal governance may hinder the achievement of business objectives. The primary aim of this research is to assess the alignment between business processes and IT strategies, identify weaknesses in IT governance, and provide recommendations for improvement. The methods used in this study include interviews, document analysis, and questionnaires. The results indicate that the integration of the APO and MEA domains can enhance the effectiveness of information system audits and provide significant added value to companies in their efforts to achieve better IT governance.